Research Progress in the Application of MOFs Coupled Wood Composites in Environmental Remediation - Rongfu PENG; Xinfeng ZHU; Junning WANG; Jinhui ZHANG; Chaohai WANG; Shangru ZHAI (工程科学与技术)
In light of the national advocacy that “green waters and green mountains are golden mountains and silver mountains,” developing advanced, recyclable pollutant removal technologies that are efficient, cost-effective, and pollution-free has become crucial. Traditional technologies such as activated carbon adsorption, advanced oxidation, and membrane separation remain prevalent due to their low cost. However, these methods often suffer from low efficiency, high energy consumption, and secondary pollution issues. Environmental nanotechnology, centered on nanomaterials (including adsorption, catalysis, and membrane separation), has attracted significant attention for its high efficiency and functional diversity. Metal-organic frameworks (MOFs), multifunctional crystalline materials composed of metal ions and organic ligands, exhibit structures ranging from one-dimensional to three-dimensional. As an emerging class of porous materials, MOFs offer promising applications in environmental remediation due to their ordered pores, rich structures, and extensive surface area. However, the crystal structure of MOFs typically results in a powdered form that is inherently fragile, unsuitable for processing, and low compatibility. These limitations hinder their recycling, processing, and molding, severely restricting their practical application. Biomass materials have attracted great interest globally due to their diversity, low cost, and inherent high porosity. Wood, one of the most common and abundant biomass materials, features a natural multidimensional pore structure, abundant hydroxyl/carboxyl groups, and good processability, making it an ideal substrate for immobilizing powdered MOFs. In recent years, scholars have used its intrinsic structure and characteristics to introduce functional nanoparticles or heterogeneous catalysts and other active components to build a new structural system with MOFs as a novel carrier, which has emerged as a current research focus and is progressively being applied in the development of biomass and its derivatives-based composites such as wood, cellulose, gel, and in the catalytic conversion of biomass. The expanding foundational research demonstrates considerable potential for application. Accordingly, this study comprehensively introduces the coupling strategies between MOFs and wood, such as mixed immersion, vacuum immersion, solvothermal, and in situ growth methods. In addition, the mechanisms of MOFs loading onto wood to a couple of MOF/wood composite materials, such as physical adsorption, the wetting mechanism, capillary phenomenon, self-growth pressure, and nucleation sites, are revealed. The study also summarizes the representative achievements in the application research of MOF materials in biomass and its derived chemicals. Based on this, the current application status of these MOF/wood composites in environmental remediation fields such as gas phase adsorption, heavy metal ion removal, harmful particle filtration, and advanced oxidation is discussed, and the correlation between the microstructure design of MOFs and the macroscopic performance of the composite materials is clarified. Finally, the opportunities and challenges faced in developing MOF/wood composite materials are explored. This review provides a new perspective on the design and construction of MOF-based composite materials for practical environmental applications, which is anticipated to enhance their application in environmental remediation.